Inter-relationship between performance of Bursa Malaysia and foreign stock markets / T. Chantrathevi P. Thuraisingam, Tew You Hoo and Dalila Daud - P. Thuraisingam, T. Chantrathevi; Tew, You Hoo; Daud, Dalila (Institute of Research, Development and Commercialization (IRDC), 2006)
This paper explores the general perception that the Malaysian stock market is influenced by leading overseas stock markets. Employing correlation analysis comparison was made between the performance ofBiirsa Malaysia's Composite Index and six stock market indices namely Straits Times Index, Hang Seng Index, Nikkei 225 Stock Average, Australia All Ordinaries Index, Dow Jones Industrial Average Index and Financial Times 100 Index. This study also seeks to determine ifthere is any significant stability ofcorrelations over time. These indices were studied over a period offifteen years from I January 1990 to 31 December 2004, beginning with the cessation oftrading ofMalaysian shares on the Singapore stock exchange, which is synonymous with the pre-Asian financial crisis period, the crisis period and a post crisis period of almost five years. The study found that the, daily returns of the Composite Index over the period is positively co-related with the foreign indices indicating that the markets were moving in the same direction, in other words there is interdependency between the stock markets. However, the low to moderate correlation refutes the belief that the Malaysian stock market is influenced by the performance ofthe major stock markets. The study also found that generally the correlations are unstable over lime.